PENGARUH PENDEKATAN PEMBELAJARAN DAN LOCUS OF CONTROL TERHADAP KEMAMPUAN PENALARAN MATEMATIKA SISWA SMP - Setiawan .; Sahat Saragih; Pargaulan Siagian (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2010)
This study aims to determine: (1) whether there are differences in mathematical reasoning ability of students who were given open-ended learning approach with students who are given conventional teaching approaches. (2) whether students' mathematical reasoning abilities that have an internal locus of control is better than students who have external locus of control on the open-ended approach to learning and conventional learning approach. (3) whether there is an interaction between learning approach with the locus of control that students have in influencing students' mathematical reasoning. The population of this study are all SMP Negeri Lhokseumawe are selected by purposive sampling SMP 11 and SMP 13 as the sample with the students as many as 135 people. This research used quasi-experimental 2x2 factorial design. The instrument used is the mathematical reasoning ability and locus of control with the reliability of each of 0.923 and 0.611. Based on the analysis of variance (ANOVA) found that: (1) there are significant differences in reasoning ability on learning approach with conventional open-ended. (2) there are significant differences in reasoning abilities in both types of locus of control, mathematical reasoning abilities of students who have internal locus of control is better than an external locus control. (3) there is no interaction between learning approach with the locus of control 's students. Based on the results of the study, researchers suggested that open-ended learning approach can be used as an alternative capable of learning to develop students' mathematical reasoning and is also able to gradually change an external locus of control students have an internal direction.